ANALISIS PENGGUNAAN SISTEM BARCODE UNTUK MENDUKUNG PAPERLESS DALAM MENINGKATKAN KEUNTUNGAN FINANSIAL DAN OPERASIONAL - Danny Ong (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2019)
The use of physical paper in the business world today has become a consideration as a waste that can affect the company's financial cycle. The saving of using documents without using physical paper is one way to reduce the company's operating costs, especially for companies that have offices and also some factories in running their businesses. The operational process of non-physical documents is supported by the use of barcodes so that the use of paper is very minimal and management can reduce the company's operational costs to the maximum. This study aims to make observations and analysis of barcode usage related to the effectiveness and efficiency in terms of employee performance and especially financial savings. The results of the study show that in terms of operational expenses of the company that there are benefits of cost savings on physical paper purchases and also employee performance is quite significantly increased in carrying out daily operations because entering data can be done semi-automatically.